UV‐Assisted One‐Step Synthesis of Ternary Graphene/Polypyrrole/Silver Nanocomposites for Supercapacitors. Issue 3 (25th January 2021) - Liang, Chunliu; Yang, Chao; Zang, Limin; Liu, Qifan; Qiu, Jianhui; Li, Yuqi; Zuo, Wusheng; Liu, Xin
Abstract : Herein, a simple and convenient one‐step method to prepare ternary graphene/polypyrrole/silver (GE/PPy/Ag) nanocomposites with UV irradiation is demonstrated. The prepared GE/PPy/Ag nanocomposites show the desired design, in which Ag nanoparticles wrapped by a PPy layer are deposited on the surface of GE. Such a structure can combine the advantages of the three components, including the large surface area of GE, high pseudocapacitance of PPy, and superior conductivity of Ag, and overcome the shortcomings of the three components, including restacking of GE, poor cycling stability of PPy, and reunion of Ag nanoparticles. In addition, the Ag nanoparticles can store/release charges via reversible Ag/Ag + redox to further improve the electrochemical performance of GE/PPy/Ag nanocomposites as supercapacitor electrodes. The GE/PPy/Ag nanocomposite prepared with 90 min UV irradiation exhibits the highest areal capacitance (294.2 mF cm −2 ), and the symmetric quasi‐solid‐state supercapacitor retains 80.1% capacitance retention after 5000 cycles. The GE/PPy/Ag nanocomposite can also be formulated as screen‐printing ink to fabricate planar micro‐supercapacitors by the screen‐printing technique, for applications in flexible energy storage devices. Abstract : Ultraviolet light is applied to promote the reduction of silver ions and polymerization of pyrrole, which simultaneously takes place on the surface of the treated graphene, forming the graphene/polypyrrole/silver (GE/PPy/Ag) nanocomposites with the desired design. Both Ag and PPy can contribute to the capacitance, and PPy/Ag can prevent the restacking of GE, which is beneficial for improving the electrochemical performance.